Co-Stimulation of BCR and Toll-Like Receptor 7 Increases Somatic Hypermutation, Memory B Cell Formation, and Secondary Antibody Response to Protein Antigen - Castiblanco, Diana P.; Maul, Robert W.; Russell Knode, Lisa M.; Gearhart, Patricia J. (Frontiers in Immunology, 2017)
The goal of immunization is to produce both a flood of antibodies to neutralize antigen and memory cells to accelerate the secondary response. To enhance the generation of memory B cells, we examined the effect of co-engaging BCR and TLR7 receptors by immunizing mice with a hapten-protein antigen, NP-CGG, and a ligand, R837 (imiquimod). During the early and late primary responses, there was no augmentation with R837 on the number of germinal center B cells or serum antibody. However, in the niche of germinal centers, R837 increased somatic hypermutation in the canonical VH1-72 gene that encodes NP-specific antibody. Increased mutation was not due to enhanced expression of activation-induced deaminase, but was likely a result of selection for high affinity B cells with altered codons in the gene. This correlated with the appearance of antigen-specific B cells with a memory phenotype, which was intrinsic to TLR7 on B cells. To determine if these memory cells produced a recall response after a secondary challenge, spleen cells from mice that were immunized with NP-CGG and R837 were adoptively transferred into muMT recipients, and boosted with NP-CGG. Cells from mice that initially received both antigen and R837 generated a robust increase in germinal center B cells, plasmablasts, plasma cells, and serum antibody, compared to their cohorts who received antigen alone. These results support the use of co-immunization with TLR7 ligands to promote vigorous memory B cell responses to protein antigens.